Pengamanan Museum Berdasarkan Tingkat Kerentanan Bangunan dan Koleksi di Museum Semarajaya - Ni Wayan Destiena Marella Apsari; Kristiawan; Ni Wayan Herawathi (PANALUNGTIK, 2023)
Old buildings that are converted into museum buildings tend to be vulnerable to damage and can threaten the integrity of both the museum building and the collections stored in the building.  This research refers to the vulnerability of building materials and collections in the Semarajaya Museum, Klungkung Regency, Bali Province. This research was conducted to answer the problem level of vulnerable building materials and museum collections, as well as museum security based on this level of vulnerability. This research combines qualitative and quantitative. Data collection techniques in this research include observation, interviews, and literature study. The collected data is processed using vulnerability level analysis and museum security theory to assist in obtaining appropriate research results. Results of this research show that most of the materials in the buildings and collections at the Semarajaya Museum are at "high", "medium", "low" and "very low" levels of vulnerability. Overall, building materials and museum collections are susceptible to several destructive agents such as fire, pollution, incorrect temperature, water, incorrect relative humidity, and light. Apart from that, the analysis of the level of vulnerability of materials requires the existence of security efforts or actions which include actions to avoid, block, detect, respond, and treat/repair.